Dibenzothiophenes in solid bitumens: Use of molecular markers to trace paleo-oil filling orientations in the Lower Cambrian reservoir of the Moxi–Gaoshiti Bulge, Sichuan Basin, southern China. (June 2017) - Chen, Zhonghong; Yang, Yueming; Wang, T.-G.; Cheng, Bin; Li, Meijun; Luo, Bing; Chen, Yong; Ni, Zhiyong; Yang, Chengyu; Chen, Tong; Fang, Ronghui; Wang, Miao
Highlights: Abundant biomarkers were obtained from over-mature pyrobitumens. Solid bitumens and paleo-oils are derived from same source kitchen/bed. Four indicators relative to DBTs were used in tracing paleo-oil filling pathways. The primary paleo-oil migration orientation from west to east was confirmed. Analysis of solid bitumen can be used to study over-mature paleo-oil reservoirs. Abstract: The Moxi–Gaoshiti (MG) Bulge of the Sichuan Basin in southwestern China is unique because of its enormous gas field in old Cambrian and Proterozoic marine strata, where oils in carbonate reservoirs have been nearly completely cracked to solid bitumen and natural gas because of high to post-mature thermal maturity levels. Numerous solid bitumen-bearing dolomites obtained from boreholes in the MG Bulge provide an ideal opportunity to trace the major filling orientations for the Lower Cambrian paleo-oil reservoirs. Biomarker analysis was conducted on solid bitumens through quantitative detection with gas chromatography–mass spectrometry. Results show that all solid bitumen samples in the MG Bulge exhibit similar compositions of molecular markers, thereby implying that they belong to the same oil population and that paleo-oils should be derived from the same source kitchen/bed. Low pristane/phytane and dibenzothiophene (DBT)/phenanthrene ratios, as well as the predominance of DBT among DBT, dibenzofuran, and fluorene, are observed in the solid bitumen samples, which suggest that related paleo-oil reservoirs likely originated from a highly reducing marine shale environment. All isopleth maps of the DBT concentrations, 4-methylDBT/1-methylDBT, 4, 6-dimethylDBT/(1, 4 + 1, 6)-dimethylDBT (DMDBT), and (2, 6 + 3, 6)-DMDBT/(1, 4 + 1, 6)-DMDBT ratios consistently indicate that the overall orientation of oil migration in the MG Bulge is primarily from the west-to-east direction, with the strongest filling point located at approximately the Mx12 well. The north-to-west direction is an additional filling orientation. These indicators show that those paleo-oils that had been cracked to pyrobitumens mainly originated from a source kitchen in the western part of the MG Bulge. A hydrocarbon source kitchen in the northern part of the MG Bulge may also have developed but further research on this is needed. The recognition of these solid bitumen molecular signatures, particularly the consistent results using DBT concentrations and alkyl DBT thermal maturity indicators, suggests a potential approach that can be applied to the study of paleo-oil reservoirs.